2011
DOI: 10.1016/j.neuroscience.2011.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure, synaptic organization, and molecular components of bushy cell networks in the anteroventral cochlear nucleus of the rhesus monkey

Abstract: Bushy cells (BCs) process auditory information in the ventral cochlear nucleus (VCN). Yet, most neuroanatomical findings come from studies in cats and rodents, and the ultrastructural morphological features of BCs in humans and higher nonhuman primates are unknown. In this study, we combined histological, immunocytochemical, and ultrastructural methods to examine the morphology and synaptic organization of BCs in the rhesus monkey VCN. We observed that BCs were organized in a complex neural network that appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 77 publications
(190 reference statements)
6
24
0
Order By: Relevance
“…This conclusion is consistent with our report of ultrastructurally characterized gap junctions between the somata of bushy cells in the rat AVCN (Gómez-Nieto and Rubio, 2009) as well as the AVCN of rhesus monkey (Gómez-Nieto and Rubio, 2011). The existence of somato-somatic and somato-dendritic gap junctions in the AVCN was reported much earlier by Sotelo and colleagues (Sotelo et al, 1976), but in this early study the cell types involved were not identified, though they too found that these gap junctions persisted after 8 th nerve deafferentation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This conclusion is consistent with our report of ultrastructurally characterized gap junctions between the somata of bushy cells in the rat AVCN (Gómez-Nieto and Rubio, 2009) as well as the AVCN of rhesus monkey (Gómez-Nieto and Rubio, 2011). The existence of somato-somatic and somato-dendritic gap junctions in the AVCN was reported much earlier by Sotelo and colleagues (Sotelo et al, 1976), but in this early study the cell types involved were not identified, though they too found that these gap junctions persisted after 8 th nerve deafferentation.…”
Section: Discussionsupporting
confidence: 93%
“…This may occur in the auditory system because, among the cell types on which we find mixed synapses, individual cells can receive collateral inputs from single auditory afferents. In the AVCN, for example, fibers forming endbulb synapses on the soma of one bushy cell can form synapses on the dendrite of another bushy cell, the so called ‘synaptic dyads’ (Gómez-Nieto and Rubio, 2009, 2011). Further, we have found examples of one auditory ending synapsing with two bushy somata (Rubio, unpublished observations), which could allow electrical coupling of those cells by way of these presynaptic fibers, even further contributing to the potential for synchronous activity of bushy cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of the geometry and synaptic organization of the dendritic arbors of bushy cells have demonstrated that bushy cells dendrites participate in a large number of compartmentalized excitatory and inhibitory synaptic interactions (Gómez-Nieto and Rubio, 2009Rubio, , 2011. The dendritic inputs on bushy cells are of both cochlear and noncochlear origin, and their proportion and distribution are dependent on the branching pattern and orientation of the dendritic arbor (Fig.…”
Section: Systemsmentioning
confidence: 99%
“…Specific sensory projection neurons to the CN originate in the trigeminal ganglion and the spinal trigeminal nucleus (Sp5) (Haenggeli, et al, 2005, Shore, et al, 2000, Zhou and Shore, 2004), dorsal root ganglion and dorsal column nuclei (Itoh, et al, 1987, Zeng, et al, 2011, Zhan, et al, 2006, Zhou and Shore, 2004), saccule and vestibular nucleus (Barker, et al, 2012, Bukowska, 2002, Burian and Gstoettner, 1988). Most of the projections from non-auditory sensory ganglia and brainstem nuclei terminate in the CN granule cell domain (GCD), but some of them end in magnocellular CN regions (Gomez-Nieto and Rubio, 2011). Anterograde and retrograde tract tracing demonstrate that the trigeminal ganglia directly innervate neurons in the cochlea, middle ear, shell area of the ventral CN (VCN) including the GCD and the fusiform cell layer of the dorsal CN (DCN).…”
Section: Multisensory Integration In the Cochlear Nucleusmentioning
confidence: 99%